Analytical modeling of disc-type permanent magnet hysteresis motor in steady-state operational conditions. Issue 4 (3rd July 2017) - Behniafar, Ali; Darabi, Ahmad
Abstract : Purpose: In this paper, a new structure for the permanent magnet hysteresis synchronous (PMHS) motor is introduced. Moreover, this paper aims to presents a new analytical method for modeling of a disc-type PMHS motor. Design/methodology/approach: Because the hysteresis and permanent magnet motors have unique characteristics, a motor (the PMHS motor) with excellent performance features can be achieved by combining them. Choosing a disc-type slotless structure causes the major advantages of both motors to be preserved in the new motor. To analyze PMHS motor, mathematical equations are obtained by using Ampere's circuital law, flux continuity law and Faraday's law. Then the air-gap voltage and exciting current of the motor can be calculated. To implement this method, a new iterative algorithm is proposed. This algorithm consists of one-iteration loop for each input voltage to find the maximum flux density of the operational hysteresis loop of the motor. Findings: Validity of the analytical approach is confirmed by experimental results. A reasonably close agreement between the two is shown and some outstanding performances of the PMHS motor are demonstrated. Originality/value: A new structure for PMHS motor and also a new analytical method for performance prediction of this motor is presented.